Genome-wide identification, evolution, and expression and metabolic regulation of the maize CHS gene family under abiotic stress - Xiaofang Wang; Jing Wu; Huangai Li; Lei Zhu; Yan Long (BMC Genomics)
Abstract Background Flavonoids are crucial for plant growth, development, and stress responses. Chalcone synthase (CHS) is a key enzyme in flavonoid biosynthesis, but its role in maize remains unclear. This study aims to dissect the gene structure, evolution, regulatory elements, and expression pattern under abiotic stress of the CHS gene family in maize, providing insights into its metabolic regulation and stress response mechanisms. Results This study identified the CHS gene family members based on maize genomic data. We analyzed their gene structures, evolutionary relationships, cis-regulatory elements, conserved motifs, tissue expression patterns, and expression profiles under various abiotic stress treatments. Furthermore, through KEGG and GO enrichment analyses, we further explored the biological diversity of the CHS gene family and its potential regulatory roles in the maize secondary metabolism network. Then, the ZmCHS25 gene was selected as a representative for functional analysis. We investigated the metabolic regulatory mechanisms during the salt stress response by constructing gene knockout mutants and combining untargeted metabolomics analysis. The results showed that its loss of function led to a dramatic decrease in flavonoid synthesis. The knockout of ZmCHS25 disrupted the phenylpropanoid metabolic pathway and impaired the osmotic regulation ability of plant cells, ultimately leading to a significant reduction under salt stress conditions. Conclusions The results reveal the evolutionary characteristics of the maize CHS gene family and clarify its metabolic regulation mechanism in response to salt stress.